2014
DOI: 10.1530/eje-13-0590
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking cessation on β-cell function, insulin sensitivity, body weight, and appetite

Abstract: Objective: To stop smoking is commonly associated with significant weight gain, but the mechanisms for this are poorly understood. We assessed the effects of smoking cessation on body weight, insulin sensitivity, b-cell function, and appetite. Subjects and methods: Twenty-seven long-term smokers (nZ27; nine females/18 males, 28G1 years, 22.9G0.6 kg/m 2 )attending an ambulatory smoking cessation program in a community hospital in Vienna, Austria were examined at baseline (Visit A; still smoking) and after a min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 67 publications
2
60
1
Order By: Relevance
“…Smoking cessation reduces the risk of cardiovascular disease (CVD) and increases life expectancy [2], but may also cause weight gain. This weight gain is a major reason for smoking recidivism and reduces incentives for smokers to quit [3,4] it may also lessen some of the health benefits of quitting smoking [5-9]. An accurate estimate of the long-term weight gain after smoking cessation is essential both for effectively designing weight-control interventions in those who quit smoking, and for assessing the potential risks associated with this weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking cessation reduces the risk of cardiovascular disease (CVD) and increases life expectancy [2], but may also cause weight gain. This weight gain is a major reason for smoking recidivism and reduces incentives for smokers to quit [3,4] it may also lessen some of the health benefits of quitting smoking [5-9]. An accurate estimate of the long-term weight gain after smoking cessation is essential both for effectively designing weight-control interventions in those who quit smoking, and for assessing the potential risks associated with this weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown different impacts of smoking on obesity. Beside the fact that nicotine is associated with decreases in appetite and calorie intake, smoking also decreases capacity of individual to perform exercise due to impact on lung functions [1][2][3]. Due to the fact that smoking has different effects on obesity, different studies showed conflicting outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Increased baseline circulating leptin also predicts higher self-reported cravings for cigarettes during smoking cessation, higher withdrawal symptoms, lower positive mood, higher distress and higher physical symptoms in smokers who have been abstinent for 24 hours (al’Absi et al 2011). Baseline leptin, however, has not been linked to relapse or abstinence following four weeks of smoking cessation (al’Absi et al 2011; Stadler et al 2014). While baseline leptin (during ad libitum smoking or smoking abstinence) may not be helpful in predicting relapse, the extent to which dynamic changes in leptin concentrations during the initial phase of a quit attempt relative to ad libitum are associated with subsequent cessation outcomes is not clear.…”
Section: Introductionmentioning
confidence: 99%